2007
DOI: 10.1002/macp.200700184
|View full text |Cite
|
Sign up to set email alerts
|

Mesh Size Control of Organic‐Inorganic Hybrid Gels by Means of a Hydrosilylation Co‐Gelation of Siloxane or Silsesquioxane and α, ω‐Non‐Conjugated Dienes

Abstract: Organic-inorganic hybrid gels have been synthesized by means of co-gelation of multi-functional cyclic siloxane, 1,3,5,7-tetramethylcyclotetrasiloxane (TMCTS), or cubic silsesquioxane, 1,3,5,7,9, 11,13,15-octakis(dimethylsilyloxy)pentacyclo-[9,5,1,1,1,1]octasilsesquioxane (POSS), as crosslinking reagents with a,v-non-conjugated dienes, a hexa-1,5-diene (HD) and deca-1,9-diene (DD) mixture, using hydrosilylation reaction with Pt catalyst. Network structures of the resulting co-gels have been quantitatively cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 26 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…The mesh size of the gels was almost independent of the monomer concentrations. Similar mesh size was detected in the TMCTS‐HD gels prepared by a hydrosilylation reaction, as previously reported . The gels synthesized by TVMCTS‐DDT show a small peak at a long relaxation time around 10 −2 s, which corresponds to the size about 5000 nm besides a sharp relaxation at a short relaxation time (< 10 −5 s), indicating inhomogeneity of the network structure.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The mesh size of the gels was almost independent of the monomer concentrations. Similar mesh size was detected in the TMCTS‐HD gels prepared by a hydrosilylation reaction, as previously reported . The gels synthesized by TVMCTS‐DDT show a small peak at a long relaxation time around 10 −2 s, which corresponds to the size about 5000 nm besides a sharp relaxation at a short relaxation time (< 10 −5 s), indicating inhomogeneity of the network structure.…”
Section: Resultssupporting
confidence: 86%
“…We simply focus on the right scheme, structure of joint‐linker molecules and reaction conditions, to build a uniform network in the gels. The authors have reported precise control of the mesh size of organic–inorganic hybrid gels prepared by addition reaction of a cyclic siloxane (1,3,5,7‐tetramethylcyclotetrasiloxane, TMCTS) or a cubic silsesquioxane (octakis(dimethylsilyloxy)silsesquioxane, POSS) with α,ω‐nonconjugated dienes (1,5‐hexadiene, HD) or 1,7‐octadiene, DD) using a Pt catalyst, as shown in Scheme . A quantitative characterization of the network structures in the gels was investigated by a scanning microscopic light scattering (SMILS), and the results cleared homogeneous network structure of those gels.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative and solution to this problem could be the use of cheaper, silsesquioxane resins which would retain the capability of functionalization and would have well-defined, 3D moieties in their structure. However, most of the cross-linked structures based on silsesquioxane cores do not have functional groups capable of producing chemical bonds to polymer, in contrast to the cage-like silsesquioxane derivatives [21][22][23][24][25][26][27][28][29][30][31][32]. The covalent incorporation of reactive silsesquioxane monomers into polymers is the greatest advantage of the proposed fillers.…”
Section: Introductionmentioning
confidence: 99%
“…We have been developing several types of organo‐gels synthesized by addition reactions between multi‐functional monomers as a source of joint parts and α,ω‐bifunctional alkyl monomers as a source of linker parts in some organic solvents, based on the joint and linker concept. In our previous studies, addition reactions of multi‐functional cyclic siloxane, cubic silsesquioxane, thiol, polyol, and acrylate, as the joint source monomers, and α,ω‐diolefins, dithiol, diazide, divinyl ether, and diamine compounds, as the linker source monomers, successfully yielded the corresponding gels in some organic solvents 4–9 . These gels formed a homogeneous network structure with an extremely narrow mesh size distribution, and their mesh size could be controlled by the methylene length of the bi‐functional alkyl monomers.…”
Section: Introductionmentioning
confidence: 99%